2008
DOI: 10.1111/j.1365-2044.2008.05637.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of a leucocyte filter to remove tumour cells from intra‐operative cell salvage blood

Abstract: SummaryThe intra-operative blood loss of 50 consecutive gynae-oncology patients undergoing surgery for endometrial, cervical or ovarian cancer was cell salvaged and filtered. In each case blood samples were taken from the effluent tumour vein, a central venous line, the cell saver reservoir, the cell salvage re-transfusion bag after processing but before filtration and from the cell salvage re-transfusion bag after processing and filtration. Samples were examined using immunohistochemical monoclonal antibody m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(82 citation statements)
references
References 51 publications
(62 reference statements)
2
79
0
1
Order By: Relevance
“…41,56 -60 Notably, several studies have indicated that leukocyte depletion filters are able to substantially reduce and remove unwanted cells and particulate materials from the salvaged blood. 61,62 Overall, intraoperative cell salvage remains a safe and effective technique in reducing allogeneic transfusions and improving patient outcomes. 17,53 On the other hand, acute normovolemic hemodilution relies on removing a part of the blood volume from the circulation and replacing it with other fluids (crystalloids or colloids) before bleeding takes place.…”
Section: Intraoperative Managementmentioning
confidence: 99%
“…41,56 -60 Notably, several studies have indicated that leukocyte depletion filters are able to substantially reduce and remove unwanted cells and particulate materials from the salvaged blood. 61,62 Overall, intraoperative cell salvage remains a safe and effective technique in reducing allogeneic transfusions and improving patient outcomes. 17,53 On the other hand, acute normovolemic hemodilution relies on removing a part of the blood volume from the circulation and replacing it with other fluids (crystalloids or colloids) before bleeding takes place.…”
Section: Intraoperative Managementmentioning
confidence: 99%
“…A third-generation leukocyte depletion filter (Imugard III-RC [Terumo]) was routinely used for autologous transfusion of cell-salvaged blood. 13,19,32 Cell salvage was stopped when the tumour capsule was exposed during parenchymal transection, and a standard aspiration device was used further to minimize shedding of tumour cell into the cell saver reservoir. 19 Cell salvage was used only during liver resection and not for extrahepatic procedures.…”
Section: Perioperative and Anesthetic Management And Surgical Techniquementioning
confidence: 99%
“…These are ex vivo studies using oncologic cell lines that are seeded in banked or fresh blood 45,[51][52][53][54][55][56] or primary tumour cells collected at the time of tumour resection 48,49,[57][58][59] and then processed via ICS and subsequent LR filtration. Together, these studies show that advanced generation LR filters are very effective in the removal of tumour cells after ICS processing (the results of experiments where tumour cells were NOT completely removed are recorded in bold print in Table 1).…”
Section: Filtrationmentioning
confidence: 99%